Stress-Induced Depression and Its Effects on Tooth Wear in Rats: A 3D Dental Scan Imaging Perspective - Preeyarat Plongniras; Sarawut Lapmanee; Natchayaporn Thonapan; Phuripong Thangsombat; Phongsakorn Janthaphim; Chanakarn Lertkarnvijai; Pattama Chailertvanitkul; Supawich Morkmued (Life)
Background: In addition to behavioral and biochemical abnormalities, a parafunction associated with temporomandibular joint disorders (TMDs) resulted in stress-induced depression in rats. Exploring how chronic stress influences molar wear in rodents provides insights into the understanding of depression, TMD, and oral health. This study aimed to conduct a three-dimensional (3D) analysis of first molar wear in an animal model of depression by comparing molar attrition and cusp variation between stressed male rats and control groups. Methods: After obtaining a validated model of depression in male rats, we obtained 3D scans of lower molars to analyze wear patterns. The 3D analysis was applied to quantify cusps’ volume and the difference in first molar cusp morphological structure. The data were then compared to identify significant morphological differences between groups side by side. Results: The analysis revealed the reduction of cusps’ volume in the depression groups. Rats exposed to depression exhibited significantly greater occlusal table wear than their control counterparts (p < 0.05). Conclusions: As dentistry moves towards greater digital imaging, understanding the impact of psychological factors on TMD becomes increasingly necessary. This study shows that stress-induced depression in rats can result in significant tooth wear, as investigated using a 3D dental scanner.